Development of Problem-Based E-LKPD Using FlipHTML5 to Enhance Critical Thinking Skills in Senior High School Economics - Okta Renaldy Tama; Siti Suprihatin; Desi Budiono (AL-ISHLAH: Jurnal Pendidikan, 2026)
The limited use of interactive learning media and the low level of students’ critical thinking skills in economics learning highlight the need for innovative instructional tools. Integrating Problem-Based Learning (PBL) with digital media such as Electronic Student Worksheets (E-LKPD) offers potential to support more active and meaningful learning. This study employed a Research and Development (RD) approach using the 4-D model (define, design, develop, disseminate). The product developed was a PBL-based E-LKPD assisted by FlipHTML5 for the topic of human needs. The feasibility of the product was evaluated through expert validation involving media, subject matter, and language experts. A limited trial was conducted with 27 tenth-grade students to assess practicality. Data were collected using validation sheets and student response questionnaires and analyzed descriptively using percentage scores. The validation results indicated that the E-LKPD achieved a high level of validity, with scores of 91% from media experts, 80% from subject matter experts, and 91% from language experts. The practicality test showed an average score of 92%, categorized as very practical. These findings suggest that the developed E-LKPD is appropriate in terms of content, design, and usability. The results indicate that the PBL-based E-LKPD assisted by FlipHTML5 is feasible as a digital learning medium and has the potential to support student engagement and learning activities in economics. However, further research is needed to examine its effectiveness in improving learning outcomes and critical thinking skills.